“The Old Village”: Yup’ik Precontact Archaeology and Community-Based Research at the Nunalleq Site, Quinhagak, Alaska - Knecht, Rick; Jones, Warren (Études Inuit Studies, 2019)
Centred on the underresearched precontact archaeology of southwest coastal Alaska, the Nunalleq project is a decade-long collaboration between the Yup’ik village of Quinhagak and the University of Aberdeen. The Nunalleq archaeological site, like countless others in the Arctic, is being rapidly destroyed by the combined effects of global warming. Newly thawed permafrost soils are extremely vulnerable to rapid marine erosion from rising sea levels and decreases in seasonal ocean ice cover. Organic artifacts at the site have been preserved in remarkably intact condition, revealing an extraordinary record of precontact Yup’ik culture. But with the disappearing permafrost, this archaeological and ecological record is gradually decomposing, and recovery and analysis has become time critical. The Nunalleq project is a community-based response to locally identified needs to both recover threatened archaeological heritage and to find new ways to reconnect young people to Yup’ik culture and tradition. The results of the project have far exceeded our original expectations. Similar collaborative efforts may be the best hope for addressing threatened archaeological heritage in the North and beyond. Au coeur de l’archéologie précontact de la côte sud-ouest de l’Alaska, encore peu connue, le projet Nunalleq est une décennie de collaboration entre le village yup’ik de Quinhagak et l’Université d’Aberdeen. Le site archéologique Nunalleq, comme d’innombrables autres sites arctique, est en train d’être rapidement détruit à cause des effets combinés du réchauffemnet climatique. Les sols du pergélisol récemment fondus sont extrêmement vulnérables à l’érosion marine rapide qui résulte de la hausse du niveau des océans et de la baisse de la banquise marine saisonnière. Les artefacts végétaux du site ont été préservés intacts grâce à de remarquables conditions, révélant un enregistrement extraordinaire de la culture yup’ik précontact. Mais avec la disparition du pergélisol, cet enregistrement archéologique et écologique se ...